Inequality Aversion, Efficiency, and Maximin Preferences in Simple Distribution Experiments: Comment - Fehr, Ernst; Naef, Michael; Schmidt, Klaus M (American Economic Review, 2006)
Inequality Aversion, Efficiency, and Maximin Preferences in Simple Distribution Experiments: Comment by Ernst Fehr, Michael Naef and Klaus M. Schmidt. Published in volume 96, issue 5, pages 1912-1917 of American Economic Review, December 2006